2015
DOI: 10.1093/arclin/acv051
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Apraxia of Speech and Oral Apraxia: Association or Dissociation?

Abstract: Acquired apraxia of speech (AOS) is a motor speech disorder that affects the implementation of articulatory gestures and the fluency and intelligibility of speech. Oral apraxia (OA) is an impairment of nonspeech volitional movement. Although many speakers with AOS also display difficulties with volitional nonspeech oral movements, the relationship between the 2 conditions is unclear. This study explored the relationship between speech and volitional nonspeech oral movement impairment in a sample of 50 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…It also corroborates the view articulated in mimesis theory that mimetic communication arose prior to and is in principle independent from, post-mimetic communication, including language [14]. This view is further supported by research on apraxia and particularly ideomotor apraxia, which specifically targets the production of pantomime [86]. These lines of evidence give us grounds to argue that once cerebral damage leads to language loss, pantomime is used to facilitate communication.…”
Section: (C) Language Impairmentsupporting
confidence: 82%
“…It also corroborates the view articulated in mimesis theory that mimetic communication arose prior to and is in principle independent from, post-mimetic communication, including language [14]. This view is further supported by research on apraxia and particularly ideomotor apraxia, which specifically targets the production of pantomime [86]. These lines of evidence give us grounds to argue that once cerebral damage leads to language loss, pantomime is used to facilitate communication.…”
Section: (C) Language Impairmentsupporting
confidence: 82%
“…), although findings from fMRI generally do not support this claim . However, dissociations between speech production and the production of nonspeech oral movements have been reported . Furthermore, a recent fMRI study has reported selectivity for letters over nonletter symbols in written production.…”
Section: Introductionmentioning
confidence: 95%
“…29,37 However, dissociations between speech production and the production of nonspeech oral movements have been reported. 38 Furthermore, a recent fMRI study 39 has reported selectivity for letters over nonletter symbols in written production. Thus, the question clearly deserves further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The postlexical phase of word production encompasses several proposed processes and a disruption of any of them could lead to overt anomia after sIS, e.g., loss of the phonological trace or a failure of sensorimotor mapping, phonological assembly, phonetic encoding, or articulatory planning (Goldrick & Rapp, 2007; Indefrey & Levelt, 2004; Indefrey, 2011; Walker & Hickok, 2015). The last of these, a failure of articulatory motor planning, often falls under a diagnosis of verbal apraxia or acquired apraxia of speech (Duffy et al, 2015; Strand, Duffy, Clark, & Josephs, 2014; Whiteside, Dyson, Cowell, & Varley, 2015). Individuals with anomia who report frequent sIS should perform poorly on tasks that rely heavily on these output processing skills, such as repetition or oral reading.…”
Section: Introductionmentioning
confidence: 99%